Performance of the Groenevelt and Grant Model for Fitting Soil Water Retention Data from Brazilian Soils - Armindo,Robson André (2019)
ABSTRACT The soil water retention curve (SWRC) is essential for vadose zone hydrological modeling and related applications. In 2004, Groenevelt and Grant (GRT) presented a mathematical model for describing the SWRC and reported its mathematical versatility and good fit to soils from a Dutch database. In order to evaluate the application of GRT to SWRCs of Brazilian soils, we aimed to analyze the performance of GRT for 72 soils from Brazil. Besides that, the obtained results with GRT for these soils were compared to the fitting performance of the most frequently used models: Brooks and Corey (BC) and van Genuchten-Mualem (VGM). The three models were fitted to available soil water retention data by minimizing the sum of square errors. The Pearson correlation coefficient (r) and the Root Mean Square Error (RMSE) were used to assess the goodness-of-fit. Results showed high correlation coefficients (r≥0.95) and small values of RMSE (RMSE ≤0.03 cm3 cm-3) for all fits. The goodness-of-fit was of similar performance for the three models with a positively correlation between them. The major difference in shape among GRT, BC, and VGM occurred in the near saturated range, while they were almost identical for low matric potentials. The exponent of GRT showed to be highly correlated with exponents of BC and VGM, but the correlation between the other shape parameters is not well defined, making a direct conversion still difficult.